Application of whole slide image markup and annotation for pathologist knowledge capture - Walter S Campbell; Kirk W Foster; Steven H Hinrichs (Elsevier, 2013)
Objective: The ability to transfer image markup and annotation data from one scanned image of a slide to a newly acquired image of the same slide within a single vendor platform was investigated. The goal was to study the ability to use image markup and annotation data files as a mechanism to capture and retain pathologist knowledge without retaining the entire whole slide image (WSI) file. Methods: Accepted mathematical principles were investigated as a method to overcome variations in scans of the same glass slide and to accurately associate image markup and annotation data across different WSI of the same glass slide. Trilateration was used to link fixed points within the image and slide to the placement of markups and annotations of the image in a metadata file. Results: Variation in markup and annotation placement between WSI of the same glass slide was reduced from over 80 μ to less than 4 μ in the x-axis and from 17 μ to 6 μ in the y-axis ( P < 0.025). Conclusion: This methodology allows for the creation of a highly reproducible image library of histopathology images and interpretations for educational and research use.